Diagnosis and Management of SJS/TEN as a Double-Edged Sword in Epilepsyorganic Mental Disorder Patients Induced by Carbamazepine: A Case Report, Dr. Radjiman Wediodiningrat Lawang Hospital - Antari Puspita Primananda (CV. Publikasi Indonesia, 2026)
Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are life-threatening cutaneous adverse drug reactions with high mortality. Carbamazepine, an aromatic anticonvulsant, is a major trigger in Southeast Asian populations due to HLA-B*15:02 genetic susceptibility. In patients with organic mental disorder (gangguan mental organik, GMO) and epilepsy, early diagnosis is often delayed because prodromal symptoms overlap with psychiatric manifestations or are masked by communication barriers. This case report aims to describe the diagnostic and emergency management challenges of carbamazepine-induced SJS/TEN in a patient with GMO and epilepsy. This case report was compiled retrospectively based on medical records and clinical documentation from Dr. Radjiman Wediodiningrat Lawang Mental Hospital. A 26-year-old female with GMO and epilepsy developed SJS/TEN overlap with 10–29% body surface area (BSA) involvement one week after carbamazepine initiation. Symptoms included high fever (39.8 °C), painful swallowing, an erythema-multiforme–like rash, bullae, and severe mucosal erosions of the lips and eyes. The Nikolsky sign was positive. Laboratory findings showed elevated liver enzymes and electrolyte imbalances. Carbamazepine and all psychiatric medications were immediately discontinued. The patient received high-dose intravenous methylprednisolone, fluid resuscitation, and supportive care before referral to a tertiary hospital. Diagnosing SJS/TEN in patients with mental disorders requires high clinical vigilance due to atypical presentations. Prompt drug withdrawal is critical despite the dilemma of seizure control. Multidisciplinary collaboration is essential for optimal management and improved prognosis.